(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic and progressive interstitial lung disease characterized by excessive fibrosis, impaired lung function, and high mortality, with limited effective treatment options. Natural products have emerged as promising sources of novel therapeutic agents due to their diverse pharmacological activities. Cardiospermum halicacabum, a medicinal plant widely used in traditional medicine, possesses anti-inflammatory, antioxidant, and immunomodulatory properties that may be beneficial in the management of fibrotic disorders. The present study aimed to characterize the bioactive metabolites present in Cardiospermum halicacabum leaf extract using Gas Chromatography–Mass Spectrometry (GC-MS) and evaluate their potential against Idiopathic Pulmonary Fibrosis through computational screening. GC-MS analysis was employed to identify the phytochemical constituents of the leaf extract, and the identified compounds were subjected to molecular docking against key fibrosis-related protein targets to assess their binding affinity and molecular interactions. In addition, the pharmacokinetic properties, drug-likeness, and ADME profiles of the promising metabolites were evaluated using in silico tools to determine their suitability as potential drug candidates. The integrated GC-MS and computational approach provides a rapid and cost-effective strategy for identifying bioactive compounds with antifibrotic potential. The findings of this study are expected to provide scientific evidence supporting the therapeutic value of Cardiospermum halicacabum and may contribute to the discovery of novel plant-derived lead molecules for the treatment of Idiopathic Pulmonary Fibrosis, thereby serving as a foundation for future experimental and clinical investigations.